Research handbook on complex project organizing - Winch, Graham M.; Brunet, Maude; Cao, Dongping (Research handbooks in business and management series, 2023)
"This Research Handbook provides a cutting-edge review of complex project organizing (CPO), and suggests fruitful avenues for future research with a focus on grand challenges and a sustainable future. Split into four sections, this Research Handbook addresses transitions within the field of CPO that could, and should, take place to achieve our shared aspirations for a better future. Featuring a team of contributors that is both interdisciplinary and geographically widespread, chapters provide a clarification of core concepts of complex project organizing, comprehensive coverage of leading theoretical perspectives for CPO, as well as a discussion of key empirical research themes. In particular, special attention is given to the implications of Industry 4.0 for complex project organizing. The Research Handbook on Complex Project Organizing develops a guiding path to help academics - both established and early career - and research students in the fields of business leadership, operations management, and knowledge management navigate through these important topics, and envision how to respond to the grand challenges we all face"--